Afforestation of Boreal Open Woodlands: Early Performance and Ecophysiology of Planted Black Spruce Seedlings - Daniel Lord (Forests, 2013)
Open lichen woodlands (LWs) are degraded stands that lack the ability to regenerate naturally due to a succession of natural and/or anthropogenic disturbances. As they represent both interesting forest restoration and carbon sequestration opportunities, we tested disc scarification and planting of two sizes of containerized black spruce (Picea mariana Mill. (BSP)) seedlings for their afforestation. We compared treatment of unproductive LWs to reforestation of harvested, closed-crown black spruce-feathermoss (BSFM) stands. After one year, seedling survival and nutritional status were equivalent among stand types but despite higher root elongation index (REI), planted seedlings in LWs had lower relative growth rate, smaller total biomass and stem diameter than those in BSFM stands. Soil fertility variables, soil temperature, nor seedling water potential, helped at explaining this early growth response. Disc scarification significantly improved seedling first-year survival, biomass and foliar nutrient concentrations of P, Ca, and Mg. Smaller planting stock showed higher REI, higher shoot water potential, and higher foliar nutrient concentration of all but one of the measured nutrients (N, P, K and Mg). Hence, preliminary results suggest that planting of smaller containerized black spruce stock, combined with disc scarification, shows potential for afforestation of unproductive LWs. The impact of the lichen mat and other potential growth limiting factors on afforestation of these sites requires further investigation.